Efektivitas STAD Berbantuan Media Ular Tangga terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Ekonomi - Marita Khariza Dini; Indri Murniawaty (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Critical thinking skills are a 21st-century skill that is very important for students. However, in learning practice, critical thinking skills are still low. This is based on the fact that students' thinking skills are still at a basic level. This condition requires learning innovations that can familiarize and improve critical thinking skills. This study aims to analyze the effectiveness of the Student Teams Achievement Division (STAD) learning model assisted by snakes and ladders media to improve students' critical thinking skills. This research method is a quasi-experimental design with a Nonequivalent Control Group Design. The research sample was X-1 as the experimental class and class X-2 students as the control class at Ky Ageng Giri High School. The experimental class was treated with STAD learning assisted by snakes and ladders, while the control class was treated with conventional learning. In each class, a pre-test and post-test were conducted. Data collection techniques used tests, observations, interviews, questionnaires, and documentation. Data were analyzed using descriptive statistics, independent sample t-tests, paired sample tests, and N-gain to determine the increase in students' critical thinking skills. The results showed that the initial abilities of both groups before treatment were the same. The paired sample test revealed a significant difference between the learning model treatments before and after the experiment. The N-gain value in the experimental class was 0.8572, indicating that the use of the snakes and ladders-assisted STAD learning model in the experimental class was highly effective. This finding demonstrates that snakes and ladders-assisted STAD learning can improve students' critical thinking skills. Therefore, the snakes and ladders-assisted STAD learning model can be used as an alternative solution for innovative learning in economics to improve students' critical thinking skills.